Non-surgical treatment for ductal carcinoma in situ of the breasts – a prospective study on patient's perspective. (2021) - Co, Michael; Lee, Andrea; Kwong, Ava
Highlights: Majority of our patients chose surgery to for DIover conservative treatment for DCIS despite oncologically safe. .ddespete ispie Patient anxiety and cost of breast surveillance are the main factors. Oncologically safe is not equivalent to standard of care. Conjoint discussion with patient is important in the management of DCIS. Abstract: Introduction: Several ongoing trials are currently investigating the feasibility and non-inferiority of active surveillance for managing low-risk DCIS. However, little is known on the proposed non-surgical treatment for DCIS from patient's perspective. Methods: A prospective cohort study was performed on 1000 consecutive patients aged 18 to 90 years old with various breast disorders between 1st July 2019 and 31st December 2019. Patients were asked about their opinions on non-surgical treatments for DCIS after thorough explanation of the clinical scenario. Results: Median age was 55 years old (Range 18 – 87). 692 patients had past history of breast cancer, 279 patients had benign breast conditions, 29 patients had borderline breast lesions. 891 (89.1%) patients opted for standard surgical excision for low-risk DCIS, most of them ( N = 757, 85.0%) decided for operative management for DCIS to avoid life-time anxiety of disease progression. Patients of older age and with history of malignant breast conditions are more likely to choose surgical treatment for DCIS ( p<0.0001 ). Of note, 112 (11.2%) patients in the cohort had history of DCIS with excision done, 111 (99.1%) patients would still decide for surgical excision as the treatment of DCIS, only 1 patient expressed the wish for conservative treatment for DCIS. Conclusion: Majority of patients decided for surgical treatment for DCIS despite being offered the condition that conservative treatment could be oncologically safe. Patient anxiety and cost of extensive breast surveillance are two important factors.